Spartacus [videorecording (DVD)] - Kubrick, Stanley; Douglas, Kirk, 1916-2020-; Olivier, Laurence, 1907-1989; Simmons, Jean, 1929-2010; Laughton, Charles, 1899-1962; Ustinov, Peter; Fast, Howard, 1914-2003 (Universal Home Video, 1998)
Spartacus is the bold gladiator slave who leads a massive slave revolt against Imperial Rome in this epic true account of man's eternal struggle for freedom.